The Implementation of Peer Teaching Technique in Reading Classes for Eight Grade Students at Junior High School - Rindu Nanda Moronica; Syofnidah Ifrianti; Sri Suci Suryawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the implementation of the Peer Teaching technique in reading instruction for junior high school students. It was conducted in response to students’ common challenges, such as low participation and limited comprehension. Peer Teaching is explored as a potential strategy because it allows students to learn collaboratively, which is expected to enhance their understanding and learning motivation. The aim of this research is to investigate how Peer Teaching is applied in English reading lessons and to describe the procedures, student involvement, and its potential contributions to learning motivation. The sampling technique used is purposive sampling. Data collection techniques include observation, interviews, and documentation. The instruments used are observation sheets, interview guidelines, and documentation notes developed based on relevant indicators of peer teaching. For data analysis, this research uses Miles and Huberman’s model, which involves data reduction, data display, and conclusion drawing. The findings are expected to provide insights into the practical use of Peer Teaching and its implications for promoting student-centered and cooperative learning in junior secondary reading instruction level.